2020
DOI: 10.1017/s0029665120008022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of protein on the composition and metabolism of the human gut microbiota and health

Abstract: The composition and metabolic activity of the bacteria that inhabit the large intestine can have a major impact on health. Despite considerable inter-individual variation across bacterial species, the dominant phyla are generally highly conserved. There are several exogenous and gut environmental factors that play a role in modulating the composition and activities of colonic bacteria including diet with intakes of different macronutrients, including protein, accounting for approximately 20% of the microbial v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 115 publications
(141 reference statements)
0
13
0
Order By: Relevance
“…Cysteine and methionine, which are sulfur-containing amino acids, are important for cancer cell growth and metabolism 50 , 51 . Hydrogen sulfide can be formed by bacteria using these sulfur-containing amino acids, which can inhibit butyrate metabolism, consequently leading to mucosal damage and inflammation of the intestinal tract 52 . In colorectal cancer, microbe-derived hydrogen sulfide seems to play a role in cancer progression and colon health 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Cysteine and methionine, which are sulfur-containing amino acids, are important for cancer cell growth and metabolism 50 , 51 . Hydrogen sulfide can be formed by bacteria using these sulfur-containing amino acids, which can inhibit butyrate metabolism, consequently leading to mucosal damage and inflammation of the intestinal tract 52 . In colorectal cancer, microbe-derived hydrogen sulfide seems to play a role in cancer progression and colon health 53 .…”
Section: Discussionmentioning
confidence: 99%
“…At the genus level, we also found that the LP and VLP diets increased the relative abundances of Turicibacter , Terrisporobacter , Clostridium_sensu_stricto_1 and UCG‐005 , and decreased the relative abundances of Lactobacillus and Streptococcus . Terrisporobacter , Clostridium_sensu_stricto_1 and UCG‐005 were reported as fiber‐degrading bacteria, 43–45 whereas Lactobacillus and Streptococcus are capable of producing amines through decarboxylation of amino acids 46–48 . This can also be generated in meat and associated with microbial activity in meat 49 .…”
Section: Discussionmentioning
confidence: 99%
“…The diet habits exert a significant impact on the microbiota composition. For instance, the consumption of plant-based protein enhances the composition of Enterococcus, Bifidobacterium, and Lactobacillus while it decreased the composition of Escherichia coli, Bacteroides, and Clostridium perfringens [33,34]. In addition, the consumption of plantbased protein enhanced the production of short chain fatty acids which in turn exerts anti-inflammatory effect during obesity and help in maintaining the mucosal barrier [35].…”
Section: Impact Of Diet On Composition Of Gut Microbiotamentioning
confidence: 99%